Phono-Morpho-Lexical Similarity of Auxiliary Morphemes of the Dictionary «Mukaddimat Al-Adab» (XII-Century) Az-Zamakhshari with Kazakh Language. /Similitud fonomorfoléxica de morfemas auxiliares del diccionario «Mukaddimat al-Adab» (siglo XII) Az-zamakhshari con la lengua Kazajo. - VLADIMIROVNA LITVINENKO, ELENA; OLEGOVNA SVIRINA, LYUDMILA; SHARAPATOVICH ZHALMAKHANOV, SHAPAGAT; ABYLZHANOVNA MARETBAYEVA, MARINA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article provides a linguistic and historical overview of the problem of integration and differentiation of kinship and affinity of languages, including the features of unions. Based on the conducted linguistic analysis, the authors come to the conclusion that if adverbs in languages of different genders and tribes of Turkic origin are the result of the integration of Turkic languages, then the division in the middle ages of Turkic languages (modern national languages, such as Kazakh, Kyrgyz, Uzbek and other languages) is the result of the division of Turkic languages into branches, groups and subgroups.RESUMEN El artículo ofrece un panorama lingüístico e histórico del problema de la integración y diferenciación del parentesco y la afinidad de lenguas, incluidas las características de las uniones. Sobre la base del análisis lingüístico realizado, los autores llegan a la conclusión de que si los adverbios en idiomas de diferentes géneros y tribus de origen turco son el resultado de la integración de idiomas turcos, entonces la división en la edad media de los idiomas turcos (idiomas nacionales modernos, como el kazajo, el kirguís, el uzbeko y otros idiomas) es el resultado de la división de los idiomas turcos en ramas, grupos y subgrupos.